Scholarship in the Digital Age: Information, Infrastructure, and the Internet - Ibironke Lawal (Issues in Science and Technology Librarianship)
The article reviews the book "Scholarship in the Digital Age: Information, Infrastructure and the Internet," by Christine L. Borgman.